Applying SEO Methods (On-Page and Off-Page) to Optimize the Ranking of the Top Herbal Atsiri Website - Chelsy Jelita Chinta Putri Herwindo; Endang Sulistiyani (Universitas Mohammad Husni Thamrin, 2026)
Search Engine Optimization (SEO) is an important strategy for improving website rankings in search engines. The website of PT. Unggul Herbal Atsiri, which operates in the herbal health product sector, still does not appear on the first page of Google search results even though it has used relevant keywords such as